2018
DOI: 10.5530/srp.2019.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Phytochemicals Isolated from Simarouba glauca DC for Inhibiting Cancers: A Review

Abstract: Simarouba glauca DC (Family: Simaroubaceae, abbreviated as S. glauca / SG), commonly known as 'Laxmitaru' or 'Paradise tree' is an eco-friendly tree that grows in tropical areas of America, The West Indies and Brazil. Nutritionally, SG has been used as a potential source of edible oil. Medicinally, the decoction prepared from SG leaves has been demonstrated to exhibit antitumor, antimalarial, antiviral activities. Objectives: Address various existing gaps in the research on Simarouba glauca and provide future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Simarouba glauca DC is rain-fed wasteland tree commonly called as ‘Laxmitaru’ or ‘Paradise tree’ belonging to the family Simaroubaceae. Different parts of the plant are being used traditionally as, antifungal, antibacterial, antioxidant ( Osagie-Eweka et al., 2016 ; Santhosh et al., 2016 ; Umesh, 2015 ), antiparasitic, antipyretic and anticancer agents ( Jose et al., 2019 ; Manasi and Gaikwad, 2011 ). The bark extract of this tree is commonly used for dysentery hence the bark is also called ‘dysentery-bark’ ( Santhosh et al., 2016 ; Manasi and Gaikwad, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simarouba glauca DC is rain-fed wasteland tree commonly called as ‘Laxmitaru’ or ‘Paradise tree’ belonging to the family Simaroubaceae. Different parts of the plant are being used traditionally as, antifungal, antibacterial, antioxidant ( Osagie-Eweka et al., 2016 ; Santhosh et al., 2016 ; Umesh, 2015 ), antiparasitic, antipyretic and anticancer agents ( Jose et al., 2019 ; Manasi and Gaikwad, 2011 ). The bark extract of this tree is commonly used for dysentery hence the bark is also called ‘dysentery-bark’ ( Santhosh et al., 2016 ; Manasi and Gaikwad, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Simaroubaceae family is well known for the presence of quassinoids, which are a class of bitter substances responsible for a variety of biological activities including anticancer activity (Bhatnagar et al, 1984;Monseur and Motte, 1983;Polonsky et al, 1978). To date about 200 quassinoids have been isolated and structures elucidated (Jose et al, 2019). Structurally, quassinoids are the products of oxidative degradation of triterpenes and have been divided in to 5.0 different groups (C18, C19, C20, C22 and C25) based on the number of carbons present in the backbone (Jose et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To date about 200 quassinoids have been isolated and structures elucidated (Jose et al, 2019). Structurally, quassinoids are the products of oxidative degradation of triterpenes and have been divided in to 5.0 different groups (C18, C19, C20, C22 and C25) based on the number of carbons present in the backbone (Jose et al, 2019). A recent study by Tung et al, (2017) demonstrated the anti-proliferative activity of quassinoids (in particular eurycomanone) isolated from the roots of Eurycoma longifolia against various cancer cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations